2021
DOI: 10.1109/access.2021.3079243
|View full text |Cite
|
Sign up to set email alerts
|

A Serial-Parallel Self-Attention Network Joint With Multi-Scale Dilated Convolution

Abstract: Semantic segmentation is a high-level task in the field of computer vision, which paves the way for the realization of a complete understanding of the scene, and has been widely used in automatic driving, human-computer interaction, virtual reality, and other aspects. Recently, the semantic segmentation method of convolutional neural networks with deep structure has been more accurate and efficient than other methods. However, there are some problems in these methods, such as the loss of information caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This study concluded that WOMAC scores of patients after surgery were significantly lower than the score before surgery ( P < 0.001), and the effective rate of treatment of patients at 6 months after surgery was 98.3%, indicating that TKA has a high value in improving the comprehensive condition of patients, accelerating their recovery after TKA, and significantly improving their quality of life. In the study of scholar Ackerman I.N, 121 cases with KOA who underwent TKA were followed up, and it was found that the WOMAC score at 3 months after surgery was (34.9 ± 5.2), while the score at 6 months after surgery was (26.4 ± 4.5), both of which were significantly lower than that before surgery ( P < 0.001) [ 16 19 ], indicating that TKA can effectively relieve the symptoms and improve the quality of life of patients. It is noteworthy that this study only investigated the curative effect of patients within 6 months after surgery, and the long-term treatment outcomes cannot be judged comprehensively.…”
Section: Discussionmentioning
confidence: 99%
“…This study concluded that WOMAC scores of patients after surgery were significantly lower than the score before surgery ( P < 0.001), and the effective rate of treatment of patients at 6 months after surgery was 98.3%, indicating that TKA has a high value in improving the comprehensive condition of patients, accelerating their recovery after TKA, and significantly improving their quality of life. In the study of scholar Ackerman I.N, 121 cases with KOA who underwent TKA were followed up, and it was found that the WOMAC score at 3 months after surgery was (34.9 ± 5.2), while the score at 6 months after surgery was (26.4 ± 4.5), both of which were significantly lower than that before surgery ( P < 0.001) [ 16 19 ], indicating that TKA can effectively relieve the symptoms and improve the quality of life of patients. It is noteworthy that this study only investigated the curative effect of patients within 6 months after surgery, and the long-term treatment outcomes cannot be judged comprehensively.…”
Section: Discussionmentioning
confidence: 99%
“…erefore, it has also helped oil painting creation find many novel and creative perspectives and speed up the creation process from a certain angle. e oil painting generation system framework [7] based on computer image processing technology is shown in Figure 1.…”
Section: Image Fusion System Of Cloud Platformmentioning
confidence: 99%
“…The attention mechanism is to select the information that is more critical to the current task from a large amount of information. Relevant studies have shown that the integration of attention mechanism and CNNs helps to enhance the spatial correlation of feature maps [ 20 – 22 ]. Bell et al [ 23 ] introduced a spatial attention mechanism into the architecture to improve the spatial relevance of the model.…”
Section: Related Workmentioning
confidence: 99%